Interfacial polymerization synergistic plasmonic grafting modification of nanofiltration membrane and preparation method and application thereof

CN122582793BActive Publication Date: 2026-10-16SHANDONG ZHAOJIN MOTIAN +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611076279.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种界面聚合协同等离子接枝改性纳滤膜,解决了现有纳滤膜选择性差、通量低和易受污染的问题;本发明同时提供了界面聚合协同等离子接枝改性纳滤膜的制备方法和应用

Benefits of technology

(1)本发明提出梯度异质结构设计理念,通过水相添加剂辅助界面聚合反应及热处理,在膜厚度方向上构建了孔径与电荷密度的梯度分布,实现离子的高效筛分与水通量的协同优化:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122582793B_ABST
    Figure CN122582793B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of nanofiltration membrane separation, and particularly relates to an interfacial polymerization and plasma grafting modified nanofiltration membrane as well as a preparation method and application thereof. Water, polyamide-amine dendritic polymer, N-aminoethyl piperazine, a surfactant, a hydrophilic agent and a composite catalyst are uniformly mixed to obtain an aqueous phase solution; trimesoyl chloride is dissolved in n-hexane to obtain an organic phase solution; a polysulfone base film is immersed in the aqueous phase solution, taken out, dried, coated with the organic phase solution on one side, and then subjected to interfacial polymerization reaction and heat treatment to obtain a functional layer-base film composite membrane; the functional layer-base film composite membrane is subjected to plasma treatment, immersed in a methacryloyl ethyl sulfobetaine solution, taken out, washed and stored in a refrigerator to obtain the interfacial polymerization and plasma grafting modified nanofiltration membrane. The application effectively solves the problems of insufficient interception precision, poor selectivity and easy pollution of a traditional nanofiltration membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanofiltration membrane separation technology, specifically relating to an interfacial polymerization synergistic plasma grafting modified nanofiltration membrane, its preparation method, and its application. Background Technology

[0002] Nanofiltration, a novel pressure-driven membrane separation technology, offers separation precision between reverse osmosis and ultrafiltration. Nanofiltration membranes typically have pore sizes of 1–2 nm, effectively filtering out macromolecules with molecular weights ranging from 200 to 1000 Daltons (Da). It is widely used in seawater desalination, dye / pharmaceutical desalination, lithium extraction from salt lakes, reclaimed water reuse, and hard water softening. Due to its significant application value in advanced drinking water treatment, industrial wastewater recycling, and selective recovery of resources, nanofiltration membrane technology has become a research hotspot in the field of membrane separation. Its core advantage stems from its unique sub-nanometer-scale tunable pore size distribution and surface charge characteristics, enabling selective solute retention through the synergistic effect of steric hindrance and the Donnan effect. With the increasing demand for precise separation in the water treatment industry, the application potential of nanofiltration membranes in scenarios such as divalent ion removal, trace pollutant retention, and high-value-added substance recovery is becoming increasingly prominent. However, commercial nanofiltration membranes currently face a trade-off effect between permeability and selectivity in practical applications, specifically manifested as: (1) insufficient retention accuracy in the selective separation of monovalent / multivalent ions; (2) reduced membrane structure stability under high-flux conditions; and (3) easy occurrence of irreversible pollution under complex water quality conditions. The above technical bottlenecks seriously restrict the promotion and application of nanofiltration membranes in the field of fine separation.

[0003] Chinese patent CN107158981A discloses a high-flux nanofiltration membrane and its preparation method. (1) A polysulfone ultrafiltration membrane is washed with an aqueous solution of ethanol or isopropanol; (2) The polysulfone ultrafiltration membrane obtained in step (1) is immersed in a reaction solution, taken out, and washed with an aqueous solution of ethanol or isopropanol to obtain an amino-modified polysulfone ultrafiltration membrane; (3) The material obtained in step (2) is immersed in a piperazine aqueous solution, taken out, and dried; (4) The material obtained in step (3) is immersed in a pyromellitic acid chloride solution and taken out; (5) The material obtained in step (4) is dried to obtain a high-flux nanofiltration membrane. However, the process steps of this patent are cumbersome, the process cycle is long, the ion selectivity is low, the cost is high, and the economics of large-scale production are poor. Summary of the Invention

[0004] The purpose of this invention is to provide an interfacial polymerization synergistic plasma grafting modified nanofiltration membrane, which solves the problems of poor selectivity, low flux and susceptibility to fouling of existing nanofiltration membranes; this invention also provides a method for preparing and applying the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane.

[0005] The structure of the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane of the present invention is a polysulfone (PSF) base membrane, a functional layer and a modified layer connected sequentially from bottom to top. The functional layer is obtained by reacting polyamide-amine dendritic polymer (PAMAM), N-aminoethylpiperazine (AEP) and trimesoyl chloride (TMC). The modified layer is obtained by plasma grafting methacryloyl ethyl sulfobetaine (SBMA) onto the functional layer.

[0006] The method for preparing the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane of the present invention includes the following steps: (1) Water, polyamide-amine dendritic polymer, N-aminoethylpiperazine, surfactant, hydrophilic agent and composite catalyst are mixed evenly to obtain an aqueous solution; pyromellitic trimethylol chloride is dissolved in n-hexane to obtain an organic solution; (2) The polysulfone-based membrane is immersed in an aqueous solution, taken out, dried, coated with an organic phase solution on one side, and then subjected to interfacial polymerization reaction and heat treatment to obtain a functional layer-base membrane composite membrane. (3) The functional layer-base membrane composite membrane is subjected to plasma treatment, soaked in methacryloyl ethyl sulfobetaine solution, taken out, washed, and refrigerated to obtain an interfacial polymerization synergistic plasma grafting modified nanofiltration membrane.

[0007] In step (1), the surfactant is sodium dodecyl sulfate (SLS), the hydrophilic agent is 3-amino-1,2-propanediol (APD), the composite catalyst is camphor sulfonic acid (CSA), and the concentration of polyamide-amine dendritic polymer in the aqueous solution is 0.10-0.20 wt.%, the concentration of N-aminoethylpiperazine is 1.00-2.00 wt.%, the concentration of surfactant is 0.40-0.70 wt.%, the concentration of hydrophilic agent is 0.20-0.40 wt.%, and the concentration of composite catalyst is 0.20-0.40 wt.

[0008] The concentration of the organic phase solution in step (1) is 0.10-0.20 wt.%.

[0009] In step (2), the immersion time is 2-5 minutes, and the immersion temperature is 30-35℃; the coating temperature is 30-35℃, and the coating amount is 0.001-0.006 g / cm³. 2 .

[0010] In step (2), the interfacial polymerization reaction takes 1-3 minutes, the interfacial polymerization reaction temperature is 30-35℃, the heat treatment temperature is 60-65℃, and the heat treatment time is 3-5 minutes.

[0011] In step (3), the plasma treatment time is 20-25 minutes and the plasma treatment temperature is room temperature.

[0012] In step (3), the concentration of the methacryloyl ethyl sulfobetaine solution is 1.5-2 g / L, the soaking temperature is 20-25℃, and the soaking time is 1.5-2 hours.

[0013] In step (3), the plasma treatment is performed using a radio frequency plasma treatment device. The conditions of the radio frequency plasma treatment device are: electrode spacing 30-35mm, chamber pressure 40-45Pa, radio frequency power 40-50W, discharge gas is air, and temperature is room temperature.

[0014] In this invention, the radio frequency plasma processing device is a conventional plasma processing equipment. The radio frequency plasma processing device uses low-pressure radio frequency capacitor discharge to generate plasma. The electrode consists of two parallel stainless steel plates with a spacing of 30-35 mm. The two electrodes are respectively connected to the radio frequency power supply terminal and the ground terminal. During the processing, a vacuum pump is used to maintain the air pressure in the chamber at 40-45 Pa. The power applied by the radio frequency power supply is 40-50 W, and the discharge gas is air. The functional layer-base film composite film is placed in the center between the two electrodes, with one side of the functional layer facing the plasma discharge area.

[0015] The application of the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane described in this invention is in the reuse of recycled water.

[0016] The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane of this invention is also suitable for the following application scenarios: deep removal of boron ions in the preparation of ultrapure water in the electronics industry, efficient separation of magnesium and lithium in the lithium ore purification process, and selective separation of dyes / salts in the zero-discharge system of dyeing and printing wastewater.

[0017] Interfacial polymerization is a technique for preparing condensation polymers at the liquid-liquid interface between acyl chlorides and compounds containing active hydrogen atoms. Plasma graft polymerization is a modification method that uses plasma technology to graft polymer chains onto the surface of polymer materials. Its core is to use highly active particles of plasma (such as free radicals or ions) to initiate a chemical reaction on the material surface, thereby grafting specific monomers onto the material surface and endowing the material with new properties (such as hydrophilicity, biocompatibility, or antibacterial properties).

[0018] The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane of this invention uses polysulfone (PSF) as the substrate. It employs interfacial polymerization technology assisted by the surfactant sodium dodecyl sulfate (SLS), the hydrophilic agent 3-amino-1,2-propanediol (APD), and the composite catalyst camphor sulfonic acid (CSA). This is combined with synergistic modification using polyamide-amine dendritic polymer (PAMAM), N-aminoethylpiperazine (AEP), and trimesoyl chloride (TMC) to construct a functional layer with high crosslinking density and high selectivity. Subsequently, methacryloyl ethyl sulfonate is grafted onto the membrane using low-temperature plasma. SBMA (sulfobetaine betaine) is used to modify the functional layer, resulting in a modified layer on the surface of the functional layer. During the preparation process, aqueous additives (surfactants, hydrophilic agents, and composite catalysts) are used to assist interfacial polymerization and surface plasma grafting, significantly improving the selective desalination rate of the membrane. Simultaneously, low-temperature plasma technology prioritizes energy supply to electrons, rather than heating the entire gas. After gaining energy, the electrons undergo collisional dissociation, ionization, and excitation of gas molecules, initiating a chemical reaction, while the overall gas remains at a low temperature. This avoids significant waste of thermal energy and significantly reduces operating energy consumption. This invention solves the problems of traditional nanofiltration membranes, such as easy fouling, poor high-temperature performance, and rapid desalination efficiency decay, and is applicable to fields such as industrial wastewater treatment, seawater desalination, and resource recovery.

[0019] SLS in the aqueous solution, as an anionic surfactant, can reduce the interfacial tension at the aqueous-organic phase interface and form an interfacial enrichment layer, thereby slowing down the diffusion rate of PAMAM and AEP into the organic phase and preventing the polymerization reaction from being too fast. APD can both form a hydrogen bond network with the aqueous monomer through hydrophilic amino groups, further stabilizing the formed polyamide and extending the reaction time window, and can also directly participate in the amidation reaction through amino groups, thus taking into account both hydrophilicity and film formation regulation. CSA, as a composite catalyst, can regulate interfacial activity, causing the reaction between acyl chloride groups and active amino groups to be concentrated in the membrane surface area rather than diffuse excessively towards the base film.

[0020] This invention prepares a nanofiltration membrane with heterogeneous charge distribution by controlling the diffusion rates of the aqueous and organic phases in interfacial polymerization to form microregions with different charge densities in the membrane; and enhances the selective permeation capability of the nanofiltration membrane for target ions by optimizing the membrane structure and surface chemical properties.

[0021] The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane of this invention exhibits colorimetric separation performance in a 20000 ppm mixed salt solution (solutes are NaCl and Na2SO4, with a mass ratio of NaCl to Na2SO4 of 1:1): SO4 2- Retention rate ≥99%, Cl - Transmittance ≥96%, Selectivity (SO4) 2- / Cl - ≥107, flux ≥50 L·m-2 ·h -1 .

[0022] The beneficial effects of this invention are as follows: (1) This invention proposes a gradient heterostructure design concept, which constructs a gradient distribution of pore size and charge density in the film thickness direction through aqueous additive-assisted interfacial polymerization reaction and heat treatment, thereby achieving efficient ion sieving and synergistic optimization of water flux: During interfacial polymerization, the diffusion rate and reaction kinetics of PAMAM and AEP monomers into the organic phase are regulated by adding three types of additives—SLS, APD, and CSA—to the aqueous phase. This results in the formation of a highly cross-linked and dense polyamide network layer near the aqueous-organic phase interface. As the monomers diffuse deeper into the organic phase, the reaction rate and degree of cross-linking gradually decrease, thus naturally forming a gradient distribution of pore size from small to large along the film thickness direction. Simultaneously, the reaction of the acyl chloride groups of PAMAM, AEP, and TMC during this process causes different charge site densities in different layers of the polyamide network. The denser charge sites are concentrated near the interface, which can effectively prevent SO42-. 2- Divalent anions pass through, while the region near the base membrane exhibits a weaker charge density, which facilitates the rapid passage of monovalent anions and water. The pore size gradient enables fine ion sieving, while the charge gradient enhances the Donnan effect. The synergy of these two factors achieves a balance between selective ion retention and high water flux, ultimately optimizing both efficient ion sieving and water flux.

[0023] (2) This invention achieves the improvement of nanofiltration membrane performance through interfacial polymerization regulation of aqueous additives to form a functional layer, and uses plasma grafting process to modify the functional layer of the nanofiltration membrane. Aqueous additives can regulate the thickness and crosslinking density of the functional layer, preventing localized over-crosslinking or pore collapse due to uncontrolled monomer diffusion during film formation. This maintains the stability of the overall functional layer thickness, pore size, and charge distribution, improving the membrane's structural controllability and performance stability. Radiofrequency plasma treatment generates a large number of free radicals on the functional layer surface. SBMA is grafted onto the functional layer surface under free radical initiation, anchoring it covalently. Simultaneously, the residual terminal amino groups of PAMAM react with the acrylate double bonds of SBMA to form CN covalent bonds, achieving double covalent bonding. This ensures the grafted chains are firmly bonded to the functional layer surface, guaranteeing uniform SBMA distribution and forming a modified layer. The grafted SBMA possesses an amphoteric structure; its hydrophilic groups synergistically interact with the hydrophilic amino groups of PAMAM to form a dense hydrophilic barrier on the functional layer surface, significantly inhibiting non-specific adsorption and fouling layer formation, thus enhancing the antifouling capability of the nanofiltration membrane.

[0024] (3) In this invention, the highly active primary amino groups on the surface of PAMAM undergo a covalent amidation reaction with the acyl chloride groups of the organic phase TMC, forming a double-crosslinked polyamide network with AEP, which simultaneously participates in the covalent amidation reaction of TMC. In this double-crosslinked polyamide network, PAMAM acts as a three-dimensional rigid crosslinking node, and AEP acts as a linear crosslinking unit. The two work together to construct a polyamide sieving network with a narrow pore size distribution and low nano-defects, thereby achieving the separation of SO4. 2- It achieves a dense retention effect for solutes; at the same time, the nanocavities within the PAMAM molecule can provide a low-resistance, continuous, and rapid transport channel for water molecules without affecting the sieving and retention accuracy, thus achieving simultaneous optimization of separation accuracy and water flux.

[0025] (4) This invention breaks through the limitations of traditional pore size distribution through molecular-level pore design strategy, and at the same time uses surface charge regulation technology to enhance the selectivity of the Donan effect; the gradient heterostructure constructed by interfacial polymerization lays the structural foundation for efficient membrane separation, and plasma grafting realizes surface hydrophilic antifouling modification to ensure long-term stable operation of the membrane; the above mechanisms work together to effectively solve the problems of insufficient retention accuracy, poor selectivity and susceptibility to fouling of traditional nanofiltration membranes. Attached Figure Description

[0026] Figure 1 This is an atomic force microscope image of the nanofiltration membrane modified by interfacial polymerization synergistic plasma grafting in Example 1.

[0027] Figure 2 This is a scanning electron microscope image of the surface of the nanofiltration membrane modified by interfacial polymerization synergistic plasma grafting in Example 1. Detailed Implementation

[0028] The present invention will be further described below with reference to embodiments.

[0029] Example 1 (1) Ultrapure water, PAMAM, AEP, SLS, APD and CSA were mixed evenly to obtain an aqueous solution with the following concentrations: PAMAM 0.10 wt.%, AEP 1.00 wt.%, SLS 0.40 wt.%, APD 0.20 wt.%, and CSA 0.20 wt.%; TMC was dissolved in n-hexane to obtain an organic solution with a concentration of 0.10 wt.%. (2) At 30°C, the polysulfone-based membrane (PSF base membrane) was immersed in an aqueous solution for 2 minutes, then removed, drained, and excess aqueous solution was removed from the surface. It was then dried by blowing with an air knife for 30 seconds to obtain the immersed PSF base membrane. Subsequently, the immersed PSF base membrane was coated on one side by a blade at 30°C at a rate of 0.001 g / cm. 2The amount of coating material was evenly applied to the organic phase solution. After coating, the interfacial polymerization reaction was carried out at 30°C for 1 minute, followed by heat treatment in a 60°C forced-air drying oven for 5 minutes to obtain the functional layer-base film composite film. (3) The functional layer-base membrane composite membrane was subjected to plasma treatment for 20 minutes using a radio frequency plasma treatment device (electrode spacing 30 mm, chamber pressure 45 Pa, radio frequency power 40 W, discharge gas is air, temperature is room temperature). Then it was soaked in a 2 g / L methacryloyl ethyl sulfobetaine solution at 25 °C for 2 hours, taken out, rinsed with deionized water, and stored in pure water at 4 °C to obtain the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane. Atomic force microscopy images of nanofiltration membranes modified by interfacial polymerization synergistic plasmonic grafting are shown below. Figure 1 Scanning electron microscope images of nanofiltration membranes modified by interfacial polymerization synergistic plasmonic grafting are shown below. Figure 2 .

[0030] Example 2 (1) Ultrapure water, PAMAM, AEP, SLS, APD and CSA were mixed evenly to obtain an aqueous solution with the following concentrations: PAMAM 0.20 wt.%, AEP 1.50 wt.%, SLS 0.70 wt.%, APD 0.40 wt.%, and CSA 0.40 wt.%; TMC was dissolved in n-hexane to obtain an organic solution with a concentration of 0.15 wt.%. (2) At 35°C, the polysulfone-based membrane (PSF base membrane) was immersed in an aqueous solution for 5 minutes, then removed, drained, and excess aqueous solution was removed from the surface. It was then dried by blowing with an air knife for 30 seconds to obtain the immersed PSF base membrane. Subsequently, a coating was applied to one side of the immersed PSF base membrane at 35°C using a blade coating method at a speed of 0.006 g / cm². 2 The amount of coating material was uniformly applied to the organic phase solution. After coating, the interfacial polymerization reaction was carried out at 35°C for 2 minutes, followed by heat treatment in a 62°C forced-air drying oven for 4 minutes to obtain the functional layer-base film composite film. (3) The functional layer-base membrane composite membrane was subjected to plasma treatment for 22 minutes using a radio frequency plasma treatment device (electrode spacing 35 mm, chamber pressure 42 Pa, radio frequency power 45 W, discharge gas is air, temperature is room temperature). Then it was soaked in a 1.8 g / L methacryloyl ethyl sulfobetaine solution at 22 °C for 1.8 hours. After that, it was taken out, rinsed with deionized water, and stored in pure water at 4 °C to obtain the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane.

[0031] Example 3 (1) Ultrapure water, PAMAM, AEP, SLS, APD and CSA were mixed evenly to obtain an aqueous solution with the following concentrations: PAMAM 0.15 wt.%, AEP 2.00 wt.%, SLS 0.60 wt.%, APD 0.30 wt.%, and CSA 0.30 wt.%; TMC was dissolved in n-hexane to obtain an organic solution with a concentration of 0.20 wt.%. (2) At 32°C, the polysulfone-based membrane (PSF base membrane) was immersed in an aqueous solution for 3 minutes, then removed, drained, and excess aqueous solution was removed from the surface. It was then dried by blowing with an air knife for 30 seconds to obtain the immersed PSF base membrane. Subsequently, the immersed PSF base membrane was coated on one side by a blade at 32°C at a rate of 0.004 g / cm. 2 The amount of coating material was uniformly applied to the organic phase solution. After coating, the interfacial polymerization reaction was carried out at 32°C for 3 minutes, followed by heat treatment in a 65°C forced-air drying oven for 3 minutes to obtain the functional layer-base film composite film. (3) The functional layer-base membrane composite membrane was subjected to plasma treatment for 25 minutes using a radio frequency plasma treatment device (electrode spacing 32 mm, chamber pressure 40 Pa, radio frequency power 50 W, discharge gas is air, temperature is room temperature). Then, it was soaked in a 1.5 g / L solution of methacryloyl ethyl sulfobetaine at 20 °C for 1.5 hours. After that, it was taken out, rinsed with deionized water, and stored in pure water at 4 °C to obtain the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane.

[0032] Comparative Example 1 Without adding PAMAM, the other operations are the same as in Example 1 to obtain a nanofiltration membrane.

[0033] Comparative Example 2 Without using the methacryloyl ethyl sulfobetaine solution, the other operations were the same as in Example 1 to obtain the nanofiltration membrane.

[0034] Comparative Example 3 Without adding AEP, the other operations are the same as in Example 1 to obtain a nanofiltration membrane.

[0035] Performance testing At 25°C, the interfacial polymerization synergistic plasma grafting modified nanofiltration membranes from Examples 1-3 and the nanofiltration membranes from Comparative Examples 1-3 were tested in a 20,000 ppm mixed salt solution (solutes were NaCl and Na2SO4, with a mass ratio of NaCl to Na2SO4 of 1:1). The performance test results are shown in Table 1. The calculation methods for flux, water permeability, rejection rate, and permeability are as follows: J = V / (Δt × S) A = J / (ΔP - Δπ) R=(1-C p / C f )×100% T=C p / C f ×100%, Where J is the flux (L·m -2 ·h -1 V is the filtration volume (L), and S is the effective filtration area (m²). 2 Δt is the filtration time (h); A is the water permeability (L·m). -2 ·h -1 ·bar -1 ΔP is the transmembrane pressure difference (bar), Δπ is the osmotic pressure difference (bar); R is the retention rate (%), and T is the permeability (%). C f To determine the concentration (mg / L) of a certain solute in the solution before testing, C p The concentration (mg / L) of a certain solute in the solution after the test. Selectivity coefficient (SO4) 2- / Cl - The calculation method for α is as follows: α=T(Cl - ) / [100%-R(SO4 2- )], Where T(Cl - ) for Cl - Transmittance (%), R(SO4) 2- SO4 2- The retention rate (%).

[0036] Table 1. Performance test results of the interfacial polymerization synergistic plasma grafting modified nanofiltration membranes in Examples 1-3 and the nanofiltration membranes in Comparative Examples 1-3.

[0037] Compared with Comparative Examples 1-3, the nanofiltration membranes in Examples 1-3 not only have higher flux and SO42--- 2- The rejection rate and membrane selectivity are greatly improved; at the same time, the water contact angle of Examples 1-3 is smaller, and the antifouling ability is better.

Claims

1. A nanofiltration membrane modified by interfacial polymerization synergistic plasma grafting, characterized in that... Its structure consists of a polysulfone-based film, a functional layer, and a modified layer connected sequentially from bottom to top. The functional layer is obtained by reacting polyamide-amine dendritic polymer, N-aminoethylpiperazine, and pyromellitic tricarboxylic acid chloride. The modified layer is obtained by plasma grafting methacryloylethyl sulfobetaine onto the functional layer. The preparation method of interfacial polymerization synergistic plasma grafting modified nanofiltration membrane includes the following steps: (1) Water, polyamide-amine dendritic polymer, N-aminoethylpiperazine, surfactant, hydrophilic agent and composite catalyst are mixed evenly to obtain an aqueous solution; pyromellitic trimethylol chloride is dissolved in n-hexane to obtain an organic solution; (2) The polysulfone-based membrane is immersed in an aqueous solution, taken out, dried, coated with an organic phase solution on one side, and then subjected to interfacial polymerization reaction and heat treatment to obtain a functional layer-base membrane composite membrane. (3) The functional layer-base membrane composite membrane is subjected to plasma treatment, soaked in methacryloyl ethyl sulfobetaine solution, taken out, washed, and refrigerated to obtain an interfacial polymerization synergistic plasma grafting modified nanofiltration membrane. In step (1), the surfactant is sodium dodecyl sulfate, the hydrophilic agent is 3-amino-1,2-propanediol, the composite catalyst is camphor sulfonic acid, the concentration of the surfactant is 0.40-0.70 wt.%, the concentration of the hydrophilic agent is 0.20-0.40 wt.%, and the concentration of the composite catalyst is 0.20-0.40 wt.%.

2. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (1), the concentration of polyamide-amine dendritic polymer in the aqueous solution is 0.10-0.20 wt.%, and the concentration of N-aminoethylpiperazine is 1.00-2.00 wt.%.

3. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... The concentration of the organic phase solution in step (1) is 0.10-0.20 wt.%.

4. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (2), the immersion time is 2-5 minutes, and the immersion temperature is 30-35℃; the coating temperature is 30-35℃, and the coating amount is 0.001-0.006 g / cm³. 2 .

5. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (2), the interfacial polymerization reaction takes 1-3 minutes, the interfacial polymerization reaction temperature is 30-35℃, the heat treatment temperature is 60-65℃, and the heat treatment time is 3-5 minutes.

6. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (3), the plasma treatment time is 20-25 minutes and the plasma treatment temperature is room temperature.

7. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (3), the concentration of the methacryloyl ethyl sulfobetaine solution is 1.5-2 g / L.

8. The interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... In step (3), the soaking temperature is 20-25℃ and the soaking time is 1.5-2 hours.

9. The application of the interfacial polymerization synergistic plasma grafting modified nanofiltration membrane according to claim 1, characterized in that... Application in wastewater reuse.

Citation Information

Patent Citations

  • High-flux nanofiltration membrane and preparation method thereof

    CN107158981A

  • Antifouling polymer for reverse osmosis and membrane comprising same

    CN112867555A

  • Polyamide nano-film with accurately adjustable ordered pore structure and preparation method of polyamide nano-film

    CN119015897A